Dialectic and Refutation in Plato and Aristotle - Spangenberg, Pilar (Revista Archai, 2022)
The papers in this dossier were written within the framework of two research projects on the refutation strategies of radical adversaries in Plato’s and Aristotle’s writings. Both projects, directed by Graciela Marcos and based in the Institute of Philosophy “Dr. Alejandro Korn” (Instituto de Filosofía “Dr. Alejandro Korn”) of the Facultad de Filosofía y Letras of the Universidad de Buenos Aires, were subsidised by the Secretaría de Ciencia y Técnica of this university and by the Agencia Nacional de Promoción Científica y Técnológica (ANCyPT), to whom we would like to express our gratitude. Special thanks also to Fabián G. Mié, who, for several years, has been working on the question of dialectic in Plato and Aristotle and with whom, even if he has not formally joined our team, we have had the good fortune to exchange ideas and discuss many of the issues related to both projects. Fabián Mié’s work is therefore added to the works presented by Lucas M. Álvarez, María E. Díaz, Martín S. Forciniti, Julián Macías and Graciela E. Marcos in this dossier.